Effect of the Adding of Natural Antioxidant in the Stored Traditional Coconut Oil on the Free Fatty Acid Value - Mahmud, Nur R. Adawiyah; Muhammad, Nuraini; Nurhalifah (Proceeding International Conference on Science and Engineering, 2021)
Abstract: Coconut oil is one of edible oil that still produce in large quantity and sell traditionally. Coconut oil that is made and sells traditionally generally easy to become rancid and cannot be stored in a longer time. One of the main factors that caused rancidity in oil is the microbial activity that may hydrolyse oil to become glycerol and free fatty acid. The antioxidant is usually added in edible oil to prevent rancidity happened. This study aims determine free fatty acid value changing in the stored traditional coconut oil that had added with some nature antioxidants. Four natural antioxidant here are cinnamon, mangosteen peel, turmeric and cassumunar ginger. The free fatty acid value was determined using acid base titration for three weeks of stored traditional coconut oil. Results show that mangosteen peel as a natural antioxidant in traditional coconut oil gives the lowest change percentage in free fatty acid value (4.2%), while other natural antioxidant shows the same and higher change percentage of free fatty acid value. Several factors that caused the antioxidant didn’t work properly are the presence of moisture and impurities of material antioxidants. However, natural antioxidants become promise alternative antioxidants in edible oil because of healthy, not harmful, easy to obtained, cheap, less volatile, and more stable at high temperatures.